COVID-19 Worry and Mental Health Among the Economically Active Population in Guangdong, China - Yong, Xin; Zhang, Li (Frontiers in Public Health, 2022)
Background: The rapid spread of COVID-19 has induced worry about the pandemic and affected individual mental health. This study aimed to access the impact of COVID-19 worry on the mental health of economically active population (EAP). Methods: An online cross-sectional survey study was conducted during the outbreak of COVID-19. The survey was completed by 1584/1708 participants (response rate 92.74%) in Guangdong, China. The 12-item General Health Questionnaire (GHQ-12) was used to evaluate their mental health status. Ordinary Least Squares (OLS) regression models were used to identify the correlation between COVID-19 worry and mental health. Results: About 42.05% respondents reported they are very worried or extremely worried about the COVID-19 pandemic. The COVID-19 worry was negatively correlated with their mental health (p<0.01), and exhibited a stronger influence on mental health of men, younger people (aged 16-45) and unemployed persons. Conclusion: Findings suggest the COVID-19 worry had resulted new inequalities in mental health among EAP. The government should provide more public reassurance and psychological support to them to mitigate the COVID-19 worry and prevent mental health disorders.